APP‐dependent glial cell line‐derived neurotrophic factor gene expression drives neuromuscular junction formation. Issue 5 (30th December 2015) - Stanga, Serena; Zanou, Nadège; Audouard, Emilie; Tasiaux, Bernadette; Contino, Sabrina; Vandermeulen, Gaëlle; René, Frédérique; Loeffler, Jean‐Philippe; Clotman, Frédéric; Gailly, Philippe; Dewachter, Use; Octave, Jean‐Noël; et al.
Abstract : Besides its crucial role in the pathogenesis of Alzheimer's disease, the knowledge of amyloid precursor protein (APP) physiologic functions remains surprisingly scarce. Here, we show that APP regulates the transcription of the glial cell line‐derived neurotrophic factor (GDNF) . APP‐dependent regulation of GDNF expression affects muscle strength, muscular trophy, and both neuronal and muscular differentiation fundamental for neuromuscular junction (NMJ) maturation in vivo. In a nerve‐muscle coculture model set up to modelize NMJ formation in vitro, silencing of muscular APP induces a 30% decrease in secreted GDNF levels and a 40% decrease in the total number of NMJs together with a significant reduction in the density of acetylcholine vesicles at the presynaptic site and in neuronal maturation. These defects are rescued by GDNF expression in muscle cells in the conditions where muscular APP has been previously silenced. Expression of GDNF in muscles of amyloid precursor protein null mice corrected the aberrant synaptic morphology of NMJs. Our findings highlight for the first time that APP‐dependent GDNF expression drives the process of NMJ formation, providing new insights into the link between APP gene regulatory network and physiologic functions.—Stanga, S., Zanou, N., Audouard, E., Tasiaux, B., Contino, S., Vandermeulen, G., René, F., Loeffler, J.‐P., Clotman, F., Gailly, P., Dewachter, I., Octave, J.‐N., Kienlen‐Campard, P. APP‐dependent glial cell line‐derived neurotrophic factor gene expression drives neuromuscular junction formation. FASEB J. 30, 1696–1711 (2016). www.fasebj.org